2013
DOI: 10.1007/s13592-013-0230-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional gel proteome analysis of honeybee, Apis mellifera, worker red-eye pupa hemolymph

Abstract: Apis mellifera Linnaeus is a holometabolous insect that undergoes complete metamorphosis in its nonfeeding pupal stage before transitioning to the adult stage. Its pupal stages are classifiable by the unique color pigmentation of its compound eyes and thorax; notably, there is a red-eye stage involving an unpigmented body that has a relatively short duration and is easy to recognize. The aim of the current study was to create a proteomic reference map of the worker red-eye pupa hemolymph. Hemolymph was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 124 publications
(162 reference statements)
3
39
0
Order By: Relevance
“…In addition to the proteomic 2D-E-MS/MS mapping of emerged honeybees, we aimed to compare these results with the hemolymph protein composition of the red-eye pupal stage described in our previous study (Erban et al 2014). The results indicated that at the end of metamorphosis/time of emergence, the honeybee hemolymph became depleted of proteins and only a few proteins remained at a higher concentration.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition to the proteomic 2D-E-MS/MS mapping of emerged honeybees, we aimed to compare these results with the hemolymph protein composition of the red-eye pupal stage described in our previous study (Erban et al 2014). The results indicated that at the end of metamorphosis/time of emergence, the honeybee hemolymph became depleted of proteins and only a few proteins remained at a higher concentration.…”
Section: Introductionmentioning
confidence: 95%
“…We did not process the hemolymph before analysis, analogous to Erban et al (2014), as the samples mixed with DeStreak containing 0.5 % IPG buffer (pH 3-10 or 4-7) were directly used for isoelectrofocusing (IEF). IEF was performed on an Ettan IPGphor 3 (GE).…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 99%
See 3 more Smart Citations